PENINGKATAN GENETIK AKTUAL DAN INTERAKSI SUMBER BENIH X LOKASI TERHADAP KADAR 1,8 CINEOLE DAN RENDEMEN MINYAK PADA KAYUPUTIH - Noor Khomsah Kartikawati; Prastyono Prastyono; Anto Rimbawanto (Jurnal Pemuliaan Tanaman Hutan, 2016)
Realized genetic gain of improved seed of cajuput from a breeding program and seed source x site interaction on the oil properties (1,8-cineole and oil yield) was evaluated through the establishment of genetic gain trials in two sites: Gunungkidul dan Ponorogo. Improved seed from two seed sources tested in the trials were first generation seedling seed orchard (SSO-1) and selected superior seed trees in the SSO-1 (SSO-2). As a control, unimproved seed from three seed sources: natural stands in Maluku (ST-1), plantation in Ponorogo (ST-2) and Gundih (ST-3) were also planted together in the trials. The genetic gain trial was established using a randomised complete clock design which consists of 5 tested seed sources, 20 treeplot, 8 replicates and spacing of 3 x 3m. The results of study showed that the realized genetic gain for the content of 1,8-cineole from SSO-2 over the controls ranged from 13.78% to 17.52% and the genetic gain of the oil yield ranged from 15.76% to 26,43%. Meanwhile the realized genetic gain for SSO-1 ranged from 2.07% to 5.42% and 10.15% to 20.30% for the content of 1,8-cineole and oil yield,respectively. The non-significance of seed source x site interaction indicates that all improved seed from the first-generation seedling seed orchard of cajuput in Paliyan are most likely to be adaptable to the varies site in Gunungkidul and Ponorogo while maintaining the high productivity in oil properties.